THE REFORM OF THE BRAZILIAN ANTI-DUMPING REGIME: A PARTIAL REVIEW OF THE DETERMINANTS AND THE IMPLICATIONS OF DECREE 8,058/2013 - Poerschke, Rafael Pentiado; Henkin, Hélio; da Silva, Ricardo Dias (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This study considers the development and reform of the anti-dumping regime in Brazil as a ratification example of the multilateral trading system proposed by the World Trade Organization (WTO). Brazil’s history of leadership in the WTO Rounds, as well as its emergence among users of temporary barriers illustrates the fact that developing countries participate, with some success, in the endorsement and strengthening of the multilateral system itself. Using the WTO Anti-Dumping Agreement (ADA) as a model for its own regulatory framework, this practice ensures that domestic legislation will have greater compliance to international obligations and avoid constraints via the Dispute Settlement Body. Finally, the case of Decree 8,058/2013 highlighted the importance that specialized agents in the middle management of the Ministry of Development, Industry and Foreign Trade (MDIC) have in the management and improvement of the Brazilian public policy.